2018
DOI: 10.2478/aoas-2018-0038
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Subclinical Ketosis and Ruminal Dysfunction in Dairy Cows

Abstract: ketosis is still an important problem which must be solved in dairy herds. early precise diagnosis and proper evaluation of the cause of the disease is essential for good management of ketosis on dairy farms. The aim of our work was to analyse the occurrence of rumen dysfunction in connection with subclinical ketosis in dairy herds and to evaluate the relationships between betahydroxybutyrate (bhb) concentration in blood and metabolic parameters in blood, urine and rumen fluid. We analysed the results of metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
2
10
1
Order By: Relevance
“…This finding supports previous research, which reported a good positive correlation between acetoacetate and total bilirubin (Kauppinen 1984;Ropstad et al 1989). Our findings regarding relations between BHBA and bilirubin but not between BHBA and ASAT are consistent with results reported by Pechová and Nečasová (2018).…”
Section: Discussionsupporting
confidence: 93%
“…This finding supports previous research, which reported a good positive correlation between acetoacetate and total bilirubin (Kauppinen 1984;Ropstad et al 1989). Our findings regarding relations between BHBA and bilirubin but not between BHBA and ASAT are consistent with results reported by Pechová and Nečasová (2018).…”
Section: Discussionsupporting
confidence: 93%
“…As a first confirmation, Yanibada et al (2020) found in the plasma of dairy cows that dimethylsulfone and formate are inversely related to methane ruminal production. A second confirmation comes from acetate, a fatty acid produced during ruminal fermentation 30 , which was significantly increased in Group G2. This fatty acid is positively related to methanogenesis 31 and can be used by animals for energetic production when bound to coenzyme A 32 .…”
Section: Discussionmentioning
confidence: 89%
“…The prognosis predicts intensive feeding of a high carbohydrate diet by cattle, leading to accumulation of short-chain fatty acids, lactic acid, and LPS in the rumen [120]. This results in an extreme drop of rumen pH reaching <5.8 for at least 3 h in a day [121]. There are two forms of ruminal acidosis; clinical (acute) and subclinical ruminal acidosis (SARA) [122].…”
Section: Metabolic Disorders 461 Ruminal Acidosismentioning
confidence: 99%